Access and use of Climate Risk Management in Agricultural Extension (CRMAE) - Belay, Berhanu; Ambaw, Gebermedihin; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Climate information services (CIS) and climate-smart agriculture (CSA) are integral to AICCRA's initiatives, offering significant potential for scaling through targeted capacity-building and collective action. AICCRA collaborates closely with development partners, agricultural extension offices, and higher education institutions to ensure widespread access to and effective use of CSA and CIS innovations, tools, and knowledge products. AICCRA, in partnership with GiZ, Ethiopian public universities, and regional agricultural offices, conducted training sessions on climate risk management (Belay et al., 2024). These sessions equipped subject-matter specialists, development agents, and facilitators with the knowledge and skills to disseminate climate insights at the grassroots level and incorporate climate knowledge products into everyday farming practices. An assessment was conducted to evaluate the relevance and contributions of the Climate Risk Management in Agricultural Extension (CRMAE) initiative. This evaluation aimed to promote sustainable practices, enhance future implementation, and refine training materials and methodologies based on participant feedback. By addressing these areas, the initiative seeks to expand training efforts nationally, strengthen the capacity of development agents, and amplify the impact of climate-smart practices in agricultural communities.